176k views
2 votes
When 0.3(4x – 8) – 0.5(–2.4x + 4) is simplified, what is the resulting expression?

A. -4.4
B. 1.2x - 2.4 + 1.2x - 2
C. 2.4x - 0.4
D. 2.4x - 4.4

2 Answers

7 votes

Answer:its B

Explanation:

I just took the quiz

User Nagashayan
by
5.9k points
5 votes

Answer:

It's the B

Explanation:

0.3*4=1.2

0.3 *(-8)=-2.4

-0.5*(-2.4x)= 1.2x

-0.5*4=-2

So it's 1.2x - 2.4 + 1.2x - 2

User Mtkopone
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.